1983
DOI: 10.1016/0092-8674(83)90316-1
|View full text |Cite
|
Sign up to set email alerts
|

Structure of E. coli 16S RNA elucidated by psoralen crosslinking

Abstract: E. coli 16S RNA in solution was photoreacted With hydro%7Methyltrimethyl-psoralen and long wave ultraviolet light. Positions of crosslinks were determined to high resolution by partially digesting the RNA with r 1 RNase, separating the crosslinked fragme~ts by two-dimensional gel electrophoresis, reversing the crosslink, and sequencing the separated frag-This method yielded the locations of crosslinks to ;t15 nucleotides.Even finer placement has been made on the basis of our knowledge of psoralen reactivity. ·… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
0
1

Year Published

1983
1983
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(71 citation statements)
references
References 39 publications
1
69
0
1
Order By: Relevance
“…Indeed, speculations on the evolution of the protein-synthesizing system have generally concluded that the RNA must have predated the protein components. The similarity in structure of protein-free 16s RNA in solution and 16s RNA in the 30s subunit (observed with psoralen crosslinking by Wollenzein et al, 1979;Thammana et al, 1979;Thompson and Hearst, 1983; and with electron microscopy) suggests that at least vestiges of the original catalytic structure remain. While Escherichia coli rRNA may no longer be able to carry out protein-free translation, it is now generally accepted that it plays an active role in ribosomal functions, Unfortunately, the dearth of structural information has allowed formulation of only simple models for how RNA operates.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Indeed, speculations on the evolution of the protein-synthesizing system have generally concluded that the RNA must have predated the protein components. The similarity in structure of protein-free 16s RNA in solution and 16s RNA in the 30s subunit (observed with psoralen crosslinking by Wollenzein et al, 1979;Thammana et al, 1979;Thompson and Hearst, 1983; and with electron microscopy) suggests that at least vestiges of the original catalytic structure remain. While Escherichia coli rRNA may no longer be able to carry out protein-free translation, it is now generally accepted that it plays an active role in ribosomal functions, Unfortunately, the dearth of structural information has allowed formulation of only simple models for how RNA operates.…”
Section: Introductionmentioning
confidence: 94%
“…Recent work with psoralen crosslinking of 16s RNA (Thompson and Hearst, 1983) has confirmed parts of the secondary structure, and has also provided evidence for new interactions that appear to be functionally important. We will discuss how these structural features may be related to specific ribosomal mechanisms.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The early experiments relied on electron microscopy to identify the positions of tertiary cross-links in the 16S RNA, but this method is not sufficiently accurate to allow an unambiguous localization of the cross-links in the sequence. Subsequently, gel electrophoretic separation of partially digested cross-linked RNA combined with photo-reversal of the psoralen reaction enabled some secondary structural crosslinks to be detected in 16S (Turner et al, 1982) and 23S (Turner & Noller, 1983) RNA, as well as a series of both secondary and tertiary cross-links in 16S RNA (Thompson & Hearst, 1983a). Following photoreversal the precise sites of psoralen reaction cannot in general be directly determined, and these cross-link assignments were therefore made on the basis of the known preference of psoralen for U residues (Bachellerie et al, 1981).…”
Section: Primary Structurementioning
confidence: 99%
“…Specific conformational 'switches' (a switch being defined as the existence of two mutually exclusive secondary structural elements) have been proposed by various authors for 16S and 23S RNA (e.g. Glotz & Brimacombe, 1980;Glotz et al, 1981;Thompson & Hearst, 1983a;Atmadja et al, 1984) and also for 5S RNA (Trifonov & Bolshoi, 1983;De Wachter et al, 1984).…”
Section: Function Of Rrnamentioning
confidence: 99%